Community’s perceptions of the police during COVID-19 in Harlem, New York, a predominantly Black community: Social and geographical dimensions - Victoria K. Ngo; Thinh T. Vu; Victoria Sunseri; Srividhya Sharma; Deborah Levine; Malcolm A. Punter; Pedro Mateu-Gelabert; Luisa N. Borrell (PLoS ONE, 2025)
Introduction Numerous demonstrations protesting policing practices towards the Black community have sprung up across the U.S. in recent years, especially during COVID-19. We examined the community’s perception of police and its association with social (e.g., a history of discrimination and community safety) and geographical (e.g., housing type and district community) factors in New York City. Methods An online survey of 393 adults in Harlem was conducted between April and September 2021. A 10-item questionnaire asked about police responsiveness, safety, and racism, with higher scores indicating more positive perception of the police. Multivariable linear regression examined the association of social and geographical factors with community perceptions of the police. Results The mean score of community’s perception of the police was 10.33 (SD = 3.73) out of 25, indicating a generally negative view. Notably, 39% doubted police’s capacity to handle mental health issues, 36% felt police were disrespectful to demonstrators, and 35% perceived police behavior as racist. In the adjusted model, younger age groups (18−29 years old: β = −2.45, 95%CI: −3.61, −1.28; 30−39 years old: β = −1.80, 95%CI: −2.82, −0.77 vs. 40−81 years old) showed significantly less favorable perceptions of the police. Higher education (associate’s or college degree: β = −0.83, 95%CI: −1.77, −0.10; bachelor’s or graduate degree: β = −2.10, 95%CI: −3.15, −1.05 vs. high school or less) and being employed (β = −2.15, 95%CI: −3.32, −0.99 vs. unemployed) were also associated with more negative perceptions. Those living in low-income housing (β = −0.87, 95%CI: −1.62, −0.12) rather than market-rate housing and facing discrimination (β = −1.94, 95%CI: −2.72, −1.16), had more negative perceptions of the police. Interestingly, community safety during COVID-19 (β = −0.63, 95%CI: −1.05, −0.20) was negatively associated with community’s perceptions of the police. No association was observed for gender and race/ethnicity. Conclusion A large proportion of Harlem residents have negative perceptions of the police, which are influenced by social and geographical factors. Implementing targeted community programs to build trust and partnerships with law enforcement may be particularly beneficial for economically disadvantaged communities exposed to violence.